Trade Off Ethics of Colonial Lecturers and Milenial Students in Critical Thinking in Indonesia Technology University (UTI) – Bali - Dwi Sihwinarti (Jurnal Ekonomi dan Bisnis Jagaditha, 2020)
This study aims to find out the Ethics of Colonial Lecturers to understand Millennial students in communicating to be able to unite their perceptions, to find out Millennial Student Ethics hold and uphold custom and culture as a guideline in communicating or democracy critically in the education and community environment to create creative ideas in innovation, and to find out the Ethical Trade Off of Colonial Lecturers and Millennial Students in Critical Thinking to improve Communication and Teaching and Learning processes in the campus environment. This research was conducted through direct experience and observation in teaching. The research method used is descriptive qualitative approach and phenomenology. The main informants are 4 students and 2 lecturers. This research was conducted at Indonesia-Bali University of Technology campus. The research results obtained that through a personal approach and understanding, the character of millennial students and treating them as a friend, friend and even a child, from a lecturer, were able to make positive changes in the world of education. Because they feel valued and even given the opportunity to express their opinions and develop creative ideas, but within the boundaries of good ethics in accordance with eastern customs that we have. So that millennial children have a character that can bring them into critical thinking to grow and develop and innovate in accordance with technology.